2013
DOI: 10.2478/vjbsd-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

General Characteristics of Thematic Villages in Poland

Abstract: In recent years, rural areas in Poland have undergone significant changes. Agricultural production is getting more and more specialized. Consequently, bonds between farmers within the same village weaken, while farmers get to socialize more with those with the same specialization, no matter the distance. As a result, social life in some of the villages declines. Simultaneously, small- and medium-scale farmers, who cannot compete with large farms, have been looking for additional, off-farm sources of income. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
1
7
0
5
Order By: Relevance
“…Theming provide opportunities for collaboration and communication, cultural development and learning, promote infrastructure improvements, and nurture nature. Authors who analyzed thematic villages (Atkočiūnienė and Vaikšnoraitė, 2012;Dombrowicz, 2013;Kloczko-Gajewska, 2013, 2014Szcesna andWelosowska, 2015, Idziak, Majewski andZmyslony, 2015;Wachter and Wytrzens, 2016; Atkočiūnienė and Kaminaitė ) do not identify the theming characteristics that influence the development of the thematic village. However, it is possible to evaluate the latent meaning of certain statements in the analyzed scientific publications about thematic villages and to assume that their development is driven by similar characteristics as other thematic objects.…”
Section: Figure 1 Model Of the Influence Of Theming Characteristics On Village Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Theming provide opportunities for collaboration and communication, cultural development and learning, promote infrastructure improvements, and nurture nature. Authors who analyzed thematic villages (Atkočiūnienė and Vaikšnoraitė, 2012;Dombrowicz, 2013;Kloczko-Gajewska, 2013, 2014Szcesna andWelosowska, 2015, Idziak, Majewski andZmyslony, 2015;Wachter and Wytrzens, 2016; Atkočiūnienė and Kaminaitė ) do not identify the theming characteristics that influence the development of the thematic village. However, it is possible to evaluate the latent meaning of certain statements in the analyzed scientific publications about thematic villages and to assume that their development is driven by similar characteristics as other thematic objects.…”
Section: Figure 1 Model Of the Influence Of Theming Characteristics On Village Developmentmentioning
confidence: 99%
“…Atkočiūnienė and Kaminaitė (2017) argue that in theme villages visitors and locals can entertain in an authentic environment. Kloczko-Gajewska (2013, found that the establishment of a thematic village encourages the community to take care of improving and adapting the village environment and infrastructure to the theme.…”
Section: Figure 1 Model Of the Influence Of Theming Characteristics On Village Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Sebuah kampung tematik juga diibaratkan sebagai pembangunan yang berorientasi pada pembentukan gagasan, topik yang khas dan unik (Kłoczko-Gajewska, 2013). Konsep kampung tematik menurut Idziak, Majewski, & Zmyślony (2015), lebih pada menawarkan masyarakat untuk terlibat proaktif, sehingga tidak hanya berbasis masyarakat akan tetapi juga penciptaan ruang kampung berciri khas yang berkelanjutan oleh masyarakat.…”
Section: Pendahuluanunclassified
“…Perencanaan konsep dan tema kampung yang kurang matang Identitas yang kemudian diangkat menjadi tema dari sebuah kampung dapat menghasilkan sebuah karakteristik yang unik dan meningkatkan nilai jual atas kampung mereka sendiri serta dapat menciptakan sumber pendapatan tambahan (Kłoczko-Gajewska, 2013). Namun, pada implementasinya terdapat beberapa faktor yang menghambat baik dari konsep maupun tema kampung seperti perencanaan konsep kampung yang kurang matang serta tema yang diangkat menjadi tema dalam suatu kampung tidak memperhatikan kondisi dan potensi lokal wilayah/kampung tersebut.…”
unclassified